2020
DOI: 10.3390/microorganisms8122054
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Infection by Mycobacterium avium subsp. paratuberculosis in the Blood of Patients with Crohn’s Disease and Control Subjects Shown by Multiple Laboratory Culture and Antibody Methods

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) has long been suspected to be involved in the etiology of Crohn’s disease (CD). An obligate intracellular pathogen, MAP persists and influences host macrophages. The primary goals of this study were to test new rapid culture methods for MAP in human subjects and to assess the degree of viable culturable MAP bacteremia in CD patients compared to controls. A secondary goal was to compare the efficacy of three culture methods plus a phage assay and four antibo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Ns, Not significance. 2010; Kuenstner et al, 2015;Kuenstner et al, 2020). Although its possible role in the onset of various autoimmune diseases has been discussed, globally limited information on this association with HT disease has been presented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ns, Not significance. 2010; Kuenstner et al, 2015;Kuenstner et al, 2020). Although its possible role in the onset of various autoimmune diseases has been discussed, globally limited information on this association with HT disease has been presented.…”
Section: Discussionmentioning
confidence: 99%
“…MAP is the causative agent of JD in ruminants, whose role has been investigated as one of the initiators of various autoimmune diseases in susceptible human hosts ( Ekundayo and Okoh, 2020 ). Some previous studies described the association of MAP with conditions such as CD, type 1 diabetes, RA, MS, lupus erythematosus, and Blue syndrome ( Naser et al., 2004 ; Masala et al., 2011 ; Naser et al., 2013 ; Kuenstner et al., 2015 ; Niegowska et al., 2015 ; Sechi and Dow, 2015 ; Dow, 2016 ; Kuenstner et al., 2017 ; Zamani et al., 2017 ; Bo et al., 2019 ; Ekundayo and Okoh, 2020 ; Kuenstner et al., 2020 ). The culture and PCR-based detection of MAP from the blood of these autoimmune patients and the supportive role of anti-MAP therapy provide helpful evidence for the zoonotic feature of MAP as Kuenstner et al explained in their study ( Naser et al., 2010 ; Kuenstner et al., 2015 ; Kuenstner et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a study of CD patients and non-CD control subjects was conducted and demonstrated the presence of viable MAP in the blood of CD patients with a significantly increased odds ratio, but also demonstrated the viable MAP organism in some of the non-CD controls (14). The study employed four different MAP culture methods and four MAP antibody tests, included 201 subjects (61 CD patients and 140 non-CD controls) and was conducted in five laboratories (14).…”
Section: Map: a Zoonotic Pathogenmentioning
confidence: 99%
“…subsp. paratuberculosis ( Map ) is one of multiple lineages of mycobacteria that have evolved over the millennia, that have acquired the ability to infect and cause disease in multiple species, including humans (1) (reviewed in Bachmann et al (2)). It is one of the major mycobacterial pathogens impacting the livestock industry and human health.…”
Section: Introductionmentioning
confidence: 99%